Opening huisvlijttentoonstelling ter gelegenheid van het 56-jarig bestaan van de ANDB. Bonn spreekt. Midden: Mug
Opening huisvlijttentoonstelling ter gelegenheid van het 56-jarig bestaan van de ANDB. Bonn spreekt. Midden: Mug.